Analysis of profitability of inland fish farming through ponds and tanks in Gujrat - Panigrahy, Shakti Ranjan; Vahoniya, Dilip (Journal of the Inland Fisheries Society of India, 2019)
Inland fisheries enjoys prime place in Indian economy. It provides employment and livelihood for fishers who solely depend on it. Gujarat ranks third in total fish production in India, but production through Inland resources is not so significant. Day by day demand of Inland fish has been increasing in this state that motivates producers’ to produce more from their impounded land resources. Analysis of profitability of Inland fishery production is a move towards improved productivity anddetermining resource use efficiency, adds value in it as it provides information for better economies scale of production. Thirty ponds have been selected in two major districts of Gujarat purposively where more than fifty four percent of productions of inland fisheries were done through ponds and tanks.Cobb Douglas production function was used for getting relevant output in this study. At the end, selling price of fish was about six times than the cost of fish production per hectare of pond. Producer was getting benefit higher than its cost of production which was a better sign of indication. Vehicle cost, Fingerling cost, feed cost and Watch and ward cost had major share in overall cost of production but feed cost, fuel cost in transportation and pond repairing cost were major cost that impact on cost of Inland fish production. Here, in this study, feed cost and fuel cost wereunderutilized whereas pond repairing cost was over utilized. If all input resources are managed efficiently profitability from Inland fisheries will have better result for the Inland Producers. Keywords Cobb Douglas Production Function, Cost of Inland Fish Production, Resource Use Efficiency